Extending the effective temperature model to the large strain hardening behavior of glassy polymers. (January 2021) - Wang, Zheliang; Guo, Jingkai; Seppala, Jonathan E.; Nguyen, Thao D.
Abstract: Amorphous polymers exhibit a viscoplastic strain hardening behavior at large strains. To describe this hardening behavior, we have developed an effective temperature model for the nonequilibrium behavior of amorphous polymers that incorporate the effects of network orientation and relaxation at large plastic deformation. The development of network orientation is introduced as a backstress that produces kinematic hardening in the stress response, while network relaxation describes the effects of temperature and strain rate on the hardening response. The model was applied to simulate the thermomechanical behavior of polycarbonate (PC) to determine the model parameters from standard dynamic frequency sweep and differential scanning calorimetry tests. The simulation results showed that the model can quantitatively capture the dependence of the hardening modulus on strain, strain rate, and temperature, as well as the unloading and reloading behavior measured in uniaxial compression tests. We applied the model to investigate the effect of plastic dissipation on the peeling of a polymer filament from a rigid substrate to guide the design of peel tests to measure the intrinsic fracture toughness of polymers fabricated by melt extrusion additive manufacturing processes.